Self-directed channel memristor for high temperature operation. (January 2017) - Campbell, Kristy A.
Abstract: Ion-conducting memristors comprised of the layered chalcogenide materials Ge2 Se3 /SnSe/Ag are described. The memristor, termed a self-directed channel (SDC) device, can be classified as a generic memristor and can tolerate continuous high temperature operation (at least 150 °C). Unlike other chalcogenide-based ion conducting device types, the SDC device does not require complicated fabrication steps, such as photodoping or thermal annealing, making these devices faster and more reliable to fabricate. Device pulsed response shows fast state switching in the 10 −9 s range. Device cycling at both room temperature and 140 °C show write endurance of at least 1 billion.